In-situ carbide reinforced aluminium metal matrix composites obtained in pulsed arc plasma discharge; Ceramics International; Vol. 51, iss. 14 - Nikitin D. S. Dmitry Sergeevich; Nassyrbayev (Nasyrbaev) A. Artur; Tsimmerman (Cimmerman) A. I. Aleksandr Igorevich; Sivkov A. A. Aleksandr Anatolyevich; Shanenkov I. I. Ivan Igorevich (2025, 2025)
Title screen